IMPLEMENTASI METODE WORDWALL BERBASIS LITERASI DIFERENSIASI UNTUK MENINGKATKAN MINAT BACA SISWA KELAS 2 DI SDN DANGDANG 1 - Yusri; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the implementation of Wordwall method based on differentiation literacy to improve reading interest in elementary school students. The study employed a mixed-methods approach with a quasi-experimental design. Research subjects involved 60 students grade 2 from SDN DANGDANG 1. Research instruments included literacy tests, reading interest questionnaires, observations, and in-depth interviews. Sampling technique used purposive sampling with experimental and control group divisions. Research results demonstrated a significant increase in students' reading interest, with an average literacy score improvement of 67.3% in the experimental group. Statistical analysis using independent t-test showed significant differences between experimental and control groups. The Wordwall method based on differentiation literacy proved effective in improving reading motivation and abilities of elementary school students.